IMPROVING THE WORKING METHODS OF CORROSION PROTECTION PIPELINES - Victoria V. Nabokova (Вестник Северо-Кавказского федерального университета, 2022)
The paper studied and analyzed by modern anticorrosion protective coatings for pipelines, the technology of their application, identified the advantages and disadvantages for each of them